Automated fluorescence lifetime imaging plate reader and its application to Forster resonant energy transfer readout of Gag protein aggregation - Alibhai,D; Kelly,DJ; Warren,S; Kumar,S; Margineau,A; Serwa,RA; Thinon,E; Alexandrov,Y; Murray,EJ; Stuhmeier,F; Tate,EW; Neil,MAA; et al. (Journal of Biophotonics, 2013)
Fluorescence lifetime measurements can provide quantitativereadouts of local fluorophore environment andcan be applied to biomolecular interactions via Fo¨ rsterresonant energy transfer (FRET). Fluorescence lifetimeimaging (FLIM) can therefore provide a high contentanalysis (HCA) modality to map protein-protein interactions(PPIs) with applications in drug discovery, systemsbiology and basic research. We present here an automatedmultiwell plate reader able to perform rapid unsupervisedoptically sectioned FLIM of fixed and livebiological samples and illustrate its potential to assayPPIs through application to Gag protein aggregationduring the HIV life cycle. We demonstrate both heteroFRETand homo-FRET readouts of protein aggregationand report the first quantitative evaluation of a FLIMHCA assay by generating dose response curves throughaddition of an inhibitor of Gag myristoylation. Z0 factorsexceeding 0.6 are realised for this FLIM FRET assay.Fluorescence lifetime plate map with representativeimages of high and low FRET cells and correspondingdose response plot.